Android-Based Technology: Development of Alternative and Augmentative Mi-Says Communication Systems for Children with Intellectual Disabilities - Alya Jilan Rizqita (JASSI ANAKKU, 2022)
This study aims to developed an android-based alternative and augmentative communication system to children intellectual disability with communication difficulted. This research method used a qualitative descriptive method to explore the information. The sample of this research is children with intellectual disabilities with complex communication needs. The result of this research is the developed of an alternative and augmentative communication system using Android-based technology called "Mi-Says" in the form of an application that can be downloaded on a cell phone to help subjects communicate. The content contained in the "Mi-Says" application is adapted to the needs of the environment, especially in the school environment. Tailored content is especially good because it will be appropriate for subjects who have difficulty expressing their wants and needs to family, teachers, or friends in the school environment. The results of this study are expected that the alternative and augmentative communication system "Mi-Says" using Android-based technology can be useful for subjects who have complex communication needs in everyday life, especially to express their needs.